Molecular diagnosis of infective endocarditis from culture-negative valve samples in a tertiary hospital in Iran - Mohammad Reza Mohammadi; Ashraf Mohabbati Mobarez; Mohammad Ali Broumand; Neda Baseri; Mina Latifian; Saber Esmaeili (Microbiology Spectrum)
ABSTRACT The aim of this study was to investigate the prevalence of Tropheryma whipplei, Chlamydia psittaci, Chlamydia pneumoniae, Legionella, Brucella, and Francisella tularensis in valve samples from endocarditis patients using the real-time PCR method at a major referral heart hospital in Iran. In this study, 146 paraffin-embedded tissue samples from the heart valves of patients with clinical and pathological evidence of infective endocarditis (IE), who underwent heart valve replacement surgery between 2016 and 2020 at Tehran Heart Center were collected. After DNA extraction from paraffin-embedded valve tissue samples, they were surveyed for the presence of T. whipplei, C. psittaci, C. pneumoniae, Legionella, Brucella, and F. tularensis using quantitative real-time PCR (qPCR). The 16S rRNA gene sequence analysis was used for accurate species identification. Based on the molecular results, T. whipplei, Chlamydia spp., and Legionella spp. were detected in 10 (6.84%), 6 (4.1%), and 3 (2.05%) valve samples, respectively. In addition, one of six positive samples for Chlamydia spp. was identified as C. psittaci. No positive samples for F. tularensis and Brucella were found. In addition, all control valve samples were negative for all investigated pathogens. The findings suggest that specific bacterial species such as T. whipplei, Chlamydia spp., and Legionella spp. are associated with the development of IE. Considering the life-threatening nature of IE, it is critical for healthcare systems to prioritize the identification of its causative agents and develop targeted treatment strategies.IMPORTANCEInfective endocarditis (IE) is a serious and potentially life-threatening condition, and it is associated with significant morbidity, mortality, and complications, making it a major concern in both global and national healthcare systems. Late diagnosis and failure to receive appropriate treatment for patients with culture-negative endocarditis caused by hard-to-grow bacteria can lead to the death of patients. Unfortunately, in Iran, less attention is paid to the role of organisms that are difficult to cultivate in laboratory settings such as Tropheryma whipplei, Chlamydia psittaci, Chlamydia pneumoniae, Legionella, Brucella, and Francisella tularensis in causing culture-negative endocarditis, and these pathogens are overlooked by infectious, cardiologists, and health officials. This study underscores the need for special attention in the diagnosis of the agents of IE.